Economic Development of Brewing Industry in the Czech Republic and Future Prospects. - Kuběnka, Michal; Myšková, Renáta; Felgrová, Monika (STEF92 Technology Ltd., 2016)
Brewing industry is crucial for Czech consumers because the Czech Republic is the first place in the world with a consumption of 144 litres per capita per year. This industry is also important for the Czech economy as an appreciable source of income for the state budget in terms of tax collection. Specifically, it is revenue 4.61 billion CZK / year on excise duty and the estimated 11.75 billion in VAT in the year 2014. Over 93% of the beer production is produced by industrial breweries which total number is 47 in the country. The article analyses the development of the brewing industry in the Czech Republic based on the latest available data from the accounting statements of 20 industrial breweries. All of the key factors are considered, especially, the factors affecting consumption and financial stability and prosperity of brewing industry. The analysis includes prediction of future developments in the susceptibility to bankruptcy through the bankruptcy model called Karas & Režňáková Index. Ability to create economic value added is then predicted using a financial model called IN05 Index with an updated threshold for credibility prediction. The analysis shows that the average ROE in the industry was 10.27% from 2012 to 2014 but the average increase of ROE between 2012 and 2014 was 0% and from 2013 to 2014 even a decrease of minus 0.10%. This implies that brewing industry is stagnating.
Ekonomický vývoj pivovarnictví v České republice a jeho vyhlídky do budoucna
Keywords: future prospects; brewing industry; Czech Republic; predikce; pivovarnictví; Česká republika